Effect of dengue hemorrhagic fever health education on knowledge and attitudes, in elementary school children in West Java, Indonesia - Kosasih, Cecep Eli; Lukman, Mamat; Solehati, Tetti; Mediani, Henny Suzana (Linguistics and Culture Review, 2021)
Background: Flooding due to Citarum river overflowing is a natural phenomenon that is almost common every year, especially for the area around Citarum Dayeuhkolot. Floods cause various health problems, such as Dengue Haemorogic Fever (DHF). The high incidence of environmental-based infectious diseases in flood-prone villages in Dayeuhkolot is caused by problems in the health determinant factor which is associated with the still low awareness of the community that supports clean and healthy lifestyle behaviors (PHBS). Objective: To determine the effect of DHF prevention education on elementary school students' knowledge and attitudes. Methods: Quasi-experimental research design with pre-test and post-test design. The study was conducted at Bojong Asih Elementary School, Pasawahan Elementary School, Cangkuang Elementary School, and Leuwi Bandung Elementary School in 2017. The samples in this study were all students in grades 4- 6 totaling 323 people. All students were given a questionnaire before the intervention and then given counseling about the prevention of DHF and given a questionnaire again to measure the level of knowledge and attitudes. Data analysis uses descriptive univariate analysis and bivariate t test. The approach method in this research uses the Integrated UKS method.